Study on the impact of allelochemicals of senna spectabilis Dc Irwin and barneby invasion in Wayanad, Kerala - Suby (Department of Forest Genetics and Tree Breeding, KSCSTE Kerala Forest Research Institute, Peechi. University of Calicut., 2025)
Invasive alien spebies, such as Senna spectabilis, pose significant threats to biodiversity, particularly in sensitive ecosystems like the Wayanad Wildlife Sanctuary in the Westem Ghats of India. Originally introduced from South America, S. spectabilis has aggressively spread in disturbed environments, outcompeting native flora and altering ecosystem dynamics. This study investigates the allelopathic potential of S. spectabilis and its impact on soil microbial communities in the sanctuary. Allelopathic effects were assessed using leaf extracts on native plant seedlings (Ailanthus tryphysa, Pongamia pinnata, Tectona grandis, Hopea parviflora, and Dendrocalamus strictus) over three years, with changes in metabolic activity, proline content, lipid peroxidation, and antioxidant enzyme activities evaluated. GC-MS analysis identified 86 bioactive phytochemicals, including phenolic compounds and terpenoids, suggesting strong allelopathic properties that contribute to the species' invasiveness. Concurrently, metagenomic analysis of soil from invaded, managed, and pristine forest areas revealed significant shifts in microbial community composition correlated with changes in soil properties such as pH, organic carbon, and nutrient levels. Canonical correspondence analysis highlighted the impact of S. spectabilis on microbial diversity, emphasizing its broader ecological implications. These findings underscore the urgent need for effective management strategies to mitigate the spread of S. spectabilis andrestore ecological balance in the Wayanad Wildlife Sanctuary.
Keywords: Senna spectabilis; invasion; Allelopathy; Microbial diversity; Wayanad Wildlife Sanctuary; Metagenomics